On the Effect of Microwave Heating on Quality Characteristics and Functional Properties of Persimmon Juice and Its Residue - Sofia Lalou (MDPI AG, 2021)
In this study, it was investigated whether integration of microwave-heating into the pretreatment step of persimmon juice processing allows the concomitant production of both functional juice and added-value solid residue from the Diospyros Kaki “Jiro” cultivar. In this direction, persimmon pulp was treated under three different microwave-heating conditions (0.7, 4.2, and 8.4 kJ/g) prior to enzymatic maceration and compared to the non-heated material. Irrespective of microwave energy employed, the proposed hybrid treatment was highly efficient in terms of juice yield (70% w/w). The mildest heating conditions resulted in juice and residue that were both of inferior quality. Intensification of the microwave energy reduced the microbial load of the juice up to 2-log without compromising the content in total soluble solids, sugars, and L-ascorbic acid. Under the most drastic conditions, the juice was enriched in gallic acid, polyphenols, and potent DPPH● scavengers, but its orange color faded and was more acidic. In parallel, the solid juice residue retained pro-vitamin A carotenoids (~278 µg retinol activity equivalents) and low-methoxy pectin (9 g/100 g DW). Overall, our findings can assist the efforts of the local juice processing industry to utilize persimmon fruits through energy-efficient technologies in a sustainable approach.